1996
DOI: 10.1038/eye.1996.6
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic holmium:YAG laser dacryocystorhinostomy

Abstract: SUMMARYThe early results of the first 50 primary endonasal laser dacryocystorhinostomies in 49 patients performed with the holmium:YAG laser are presented. Overall, 35 (70%) were successful in relieving symptoms of naso lacrimal obstruction after a mean follow-up period of 4 months. This improved to 79% in the subgroup of patients who underwent intubation of the naso-Iacrimal system. These results were similar to the results of a retrospective study of 67 patients undergoing conven tional dacryocystorhinostomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 12 publications
2
30
0
2
Order By: Relevance
“…2 EEL-DCR is often performed as day-case surgery under local anaesthesia using the holmium:YAG or the KTP laser. 3,5,7,11,16 Advantages of EEL-DCR over EES-DCR include even less blood loss during surgery and shorter operating time. These advantages make EEL-DCR suitable, for example, for the frail elderly patient, who otherwise might not be fit for longer lacrimal surgery, either under local or under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 EEL-DCR is often performed as day-case surgery under local anaesthesia using the holmium:YAG or the KTP laser. 3,5,7,11,16 Advantages of EEL-DCR over EES-DCR include even less blood loss during surgery and shorter operating time. These advantages make EEL-DCR suitable, for example, for the frail elderly patient, who otherwise might not be fit for longer lacrimal surgery, either under local or under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The perceived disadvantages of the highly successful external approach dacryocystorhinostomy (DCR) [17][18][19][20][21] include the risk of cutaneous scar and lengthy surgery with significant blood loss. These reservations have fuelled the popularity of minimally invasive endonasal approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was statistically significant. Sadiq et al (1996) have also shown a higher success rate of ELDCR with intubation (79%) versus no intubation (59%) although these results did not reach statistical significance. In their medium term follow-up study (1997) all new patients had intubation based on these findings, so statistical significance was not achieved in this comparison between the groups.…”
Section: Discussionmentioning
confidence: 86%
“…8,9 The benefits of endonasal laser DCR are well established in adults with success rates between 63 and 97%. [10][11][12][13][14][15][16] Its role in children is yet to be evaluated and to date there has been only one case-series using the KTP laser with 0% success. 17 We describe our experience with the Holmium : YAG laser using a modified technique in these cases with promising results.…”
Section: Introductionmentioning
confidence: 99%